HUBUNGAN ANTARA POWER TUNGKAI, KOORDINASI MATA-TANGAN, DAN RASA PERCAYA DIRI DENGAN HASIL KEMAMPUAN LAY-UP SHOOT BOLA BASKET - Haetami, Mimi (Universitas Tanjungpura, 2019)
AbstactThe purpose of this study, to find out how much the relationship between power limbs, eye-hand coordination, and a sense of confidence with the results of the ability to shoot shoots on basketball.This research method uses a correlation method with product moment calculation techniques. The sample amounted to 20 people from all extra-basketball players / athletes in SMK Negeri 4 Kota Pontianak.The calculation results obtained show; 1). There is a positive relationship between Leg Power (X1) with the results of Lay-up Shoot (Y) skills of 68%. 2). There is a positive relationship between hand eye coordination (X2), with the results of Lay-up Shoot skills (Y ) of 42.2%. 3) There is a positive relationship between self-confidence (X3) and the results of Lay-up Shoot (Y) skills of 47.5%.Thus there is a positive relationship between power limbs (X1) eye-hand coordination (X2) and self-confidence (X3) together towards the results of the Lay-up Shoot skill (Y) obtained from the R correlation coefficient of 81.8% . So the conclusions from this study show that power limbs, eye-hand coordination, and self-confidence have a significant relationship with the results of basketball shoot lay-up capabilities.Keywords: Lay-up, Leg Power, Hand Eye Coordination, Confidence